2006
DOI: 10.1038/modpathol.3800705
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical markers in diagnosis of papillary thyroid carcinoma: utility of HBME1 combined with CK19 immunostaining

Abstract: Papillary thyroid carcinoma and its variants can be difficult to distinguish from cellular adenomatous nodules. Prior studies have advocated various antibodies to aid in the differential diagnosis, but there is little agreement on their utility. We undertook this study to evaluate immunohistochemical markers in the diagnosis and differential diagnosis of papillary thyroid carcinoma. Ten cases of papillary thyroid carcinoma were initially stained for HBME1, CK19, fibronectin1, Ki-67, Calretinin, p16, SFTPB and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
114
1
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 118 publications
(129 citation statements)
references
References 21 publications
11
114
1
3
Order By: Relevance
“…12,13 In the same study, it was deemed nonspecific because it also stained 68.4% of BTN cases, findings confirmed by other authors. 13,18 Although CK19 may focally stain benign lesions, diffuse and strong staining is considered typical of PTC, with a proposed cutoff value of !10% immunoreactive cells to differentiate carcinomas from adenomas. 11,16,17 The combination of HBME-1 and CK19 has been proposed to demonstrate the highest diagnostic value for the differential diagnosis of PTC, with specificity values for the diagnosis of PTC of up to 100% when coexpression of HBME-1 and CK19 is demonstrated.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…12,13 In the same study, it was deemed nonspecific because it also stained 68.4% of BTN cases, findings confirmed by other authors. 13,18 Although CK19 may focally stain benign lesions, diffuse and strong staining is considered typical of PTC, with a proposed cutoff value of !10% immunoreactive cells to differentiate carcinomas from adenomas. 11,16,17 The combination of HBME-1 and CK19 has been proposed to demonstrate the highest diagnostic value for the differential diagnosis of PTC, with specificity values for the diagnosis of PTC of up to 100% when coexpression of HBME-1 and CK19 is demonstrated.…”
Section: Discussionsupporting
confidence: 76%
“…10,11 Its utility in thyroid carcinomas has been documented in several studies, revealing strong and diffuse cytoplasmic staining in PTCs. [12][13][14][15][16][17] It is considered the most specific marker (96%) for PTC by some authors, and the most sensitive and specific marker by others, reportedly staining 96% of PTCs and only 7% of BTN cases. 12,13 Other studies have demonstrated that immunoreactivity for HBME-1 is an indication of thyroid malignancy, but not necessarily of papillary differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations